ANALISIS PENYEBAB TERJADINYA ZERO POWER PADA COMBINER BOX DI PT. INFRASTRUKTUR TERBARUKAN CEMERLANG PLTS SENGKOL LOMBOK TENGAH MENGGUNAKAN PROBLEM TREE - Mashabai, Ismi; Adiasa, Iksan (Fakultas Teknologi Lingkungan dan Mineral - Universitas Teknologi Sumbawa, 2024)
Solar Power Plants (PLTS) are electrical power generators that convert solar energy into electrical power. One of the companies engaged in electricity generation is PT. Brilliant Renewable Infrastructure. The problem that often occurs in PLTS is zero power in the combiner box. Zero power is a problem that often occurs which causes the energy produced by the PV module to not be optimal. The aim of this research is to analyze the causes of zero power in the combiner box. One way to find out the factors causing zero waste is to use a Problem Tree. Problem Tree is a methodology/technique used to identify the reasons for a problem. The results showed that the factors causing zero power in the combiner box were three causes, namely the cable gland installation was not tight enough, the DC cable was bitten by rats and the strings were not functioning. The impact of these 3 types of damage can cause zero power so that no electrical voltage is generated